Activated partial thromboplastin time (APTT) in dogs tested by in-house crude cephalin from canine brain - Sarawut Yama (2018)
This research aimed to identify the reference value of activated partial thromboplastin time (APTT) in normal dogs using crude cephalin prepared in-house from canine brain, and to examine its efficacy in detecting disorders of coagulation factors. A total of 105 blood samples were collected from normal dogs between January-May 2010. The APTT value was found to be 10.43-19.08 seconds and significantly correlated with the APTT value of a test using a commercial reagent (Pearson's correlation, r = 0.9923, p < 0.001). On testing the reagent's efficacy in detecting disorders of coagulation factors by using cryopoor plasma, it was discovered that the APTT value ranged from 24.50 to 33.44 seconds, and the mean value of the APTT by means of cryopoor plasma was significantly greater than that of normal dogs (p < 0.001). The aforementioned APTT value significantly correlated with that obtained by means of a commercial reagent (Pearson's correlation, r = 0.9984, p < 0.001). From this research, it can be confirmed that in-house crude cephalin can be substituted for commercial crude cephalin. Besides, the obtained reference range can further be applied in veterinary hematology laboratory.